2022
DOI: 10.1038/s42003-022-04110-4
|View full text |Cite
|
Sign up to set email alerts
|

First direct evidence for direct cell-membrane penetrations of polycationic homopoly(amino acid)s produced by bacteria

Abstract: Bacteria produce polycationic homopoly(amino acid)s, which are characterized by isopeptide backbones. Although the biological significance of polycationic homopoly(amino acid)s remains unclear, increasing attention has recently been focused on their potential use to achieve cellular internalization. Here, for the first time, we provide direct evidence that two representative bacterial polycationic isopeptides, ε-poly-l-α-lysine (ε-PαL) and ε-oligo-l-β-lysine (ε-OβL), were internalized into mammalian cells by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Surprisingly, we also showed that the covalent coupling between PGua 4 and IgGs allowed IgG internalization in endosomes but did not support IgG delivery into the cytosol. This result was unexpected given that most Arg-rich CPPs, such as Tat and oligo-Arg, have been shown to deliver their cargo when covalently linked to them. This suggests that either covalent binding altered the endosomal escape properties of PGua 4 , as previously reported for other CPPs, or that the ratio of IgGs-PGua 4 was not optimal . Indeed, four PGua 4 peptoids were covalently linked to each IgG, whereas many more PGua 4 peptoids may be complexed to each IgG using the noncovalent complexation method.…”
Section: Discussionmentioning
confidence: 93%
“…Surprisingly, we also showed that the covalent coupling between PGua 4 and IgGs allowed IgG internalization in endosomes but did not support IgG delivery into the cytosol. This result was unexpected given that most Arg-rich CPPs, such as Tat and oligo-Arg, have been shown to deliver their cargo when covalently linked to them. This suggests that either covalent binding altered the endosomal escape properties of PGua 4 , as previously reported for other CPPs, or that the ratio of IgGs-PGua 4 was not optimal . Indeed, four PGua 4 peptoids were covalently linked to each IgG, whereas many more PGua 4 peptoids may be complexed to each IgG using the noncovalent complexation method.…”
Section: Discussionmentioning
confidence: 93%
“…They proposed that the higher toxicity of streptothricins A-E and X compared to streptothricin F may be due to greater host cellular uptake as a result of their longer β-lysine homopolymer tails (Fig. 2a) 65 . A result of this difference in cytotoxicity is that pure streptothricin F, as opposed to a mix of streptothricins, may have a wide enough therapeutic window to justify its use against multidrug-resistant pathogens.…”
Section: Streptothricin Use In Industry Agriculture and Medicinementioning
confidence: 99%
“…Moreover, these cationic bacterial polymers could be conjugated to large antibodies (IgG, 150 kDa), which were directly delivered into the cytosol and nucleus. [82] Besides cell-penetrating peptides and polymers, various nanoparticles have also been shown to be capable of membrane penetration. [77] Löwen and co-workers developed a simple model to describe the interaction of active particles with minimal membranes, which allows for both penetrations of the membrane (with and without healing) and membrane trapping (endocytosis) (Figure 7e-g).…”
Section: Delivery Across Membranesmentioning
confidence: 99%
“…Moreover, these cationic bacterial polymers could be conjugated to large antibodies (IgG, 150 kDa), which were directly delivered into the cytosol and nucleus. [ 82 ]…”
Section: Delivery Across Membranesmentioning
confidence: 99%